(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article presents the results of a critical review of Bulgarian legislation in the field of circular economy. It also defines recommendations and guidelines on creating favourable conditions for transition from linear to circular models based on all life cycle stages of processes, products and services. The main analysed policy document, directly addressing circular economy, is the Strategy and Action Plan for the transition to a circular economy of the Republic of Bulgaria for the period 2022-2027. It lays down the strategic framework towards achieving resource efficiency by applying waste management hierarchy, i.e. waste prevention, reuse and recovery through recycling, reducing landfilling and limiting harmful impact on the environment and human health. The main pieces of legislation relevant to circular economy are the Waste Management Act and by-laws implementing Directive 2008/98/EC on waste (Waste Framework Directive), Directive 94/62/EC on packaging and packaging waste (Packaging Waste Directive), Directive 1999/31/EC on the landfill of waste (Landfill Directive), Directives 2000/53/EC on end-of-life vehicles, 2006/66/EC on batteries and accumulators and waste batteries and accumulators, and 2012/19/EC on waste electrical and electronic equipment, etc. The review of provisions in the Waste Management Act and Local Taxes and Fees Act on implementing the ‘Waste Management Hierarchy’ and ‘Polluter Pays’ principles shows the need to promote economic incentives. Bulgarian municipalities should revise their ordinances and calculate local waste fees based on the quantity of waste generated (also requested by the current EC infringement procedure for failure to implement the ‘Polluter Pays’ principle at municipal level). ‘Eco design’ provisions are in place, and provisions protecting customers’ right to repair are expected. In addition to implementing EU acquis, it is possible to promote further measures to reduce environmental impact of products throughout their entire life cycle. The critical review also overs the main documents tackling climate challenges, i.e., the Climate Change Mitigation Act and by-laws, and the National Strategy and Action Plan by 2030 for adaptation to climate change of the Republic of Bulgaria, defining the framework for actions for adaptation to climate change and priority directions. The review of ‘horizontal’ environmental legislation of the Republic of Bulgaria, i.e., provisions of the Environmental Protection Act and by-laws on strategic environmental assessment (SEA), environmental impact assessment (EIA) and integrated pollution prevention and control (IPPC), reveals the potential to address circular economy aspects in the recommendations issued as part of the relevant competent authorities’ permits. Other potential areas are the environmental protection standards and ESG (Environmental, Social, and Governance) as a framework for environmental and social impact. Last but not least, the review considers circular economy financing opportunities.